Two way controls of apoptotic regulators consign DmArgonaute-1 a better clasp on it. - Mondal, T.; Bag, I.; Sncvl, P.; Garikapati, K.R.; Bhadra, U.; Pal Bhadra, M. (PLoS ONE, 2018)
Argonaute family proteins are well conserved among all organisms. Its role in mitotic cell cycle progression and apoptotic cell elimination is poorly understood. Earlier we have established the contribution of Ago-1 in cell cycle control related to G2/M cyclin in Drosophila. Here we have extended our study in understanding the relationship of Ago-1 in regulating apoptosis during Drosophila development. Apoptosis play a critical role in controlling organ shape and size during development of multi cellular organism. Multifarious regulatory pathways control apoptosis during development among which highly conserved JNK (c-Jun N-terminal kinase) pathway play a crucial role. Here we have over expressed Ago-1 in Drosophila eye and brain by employing UAS (upstream activation sequence)-GAL4 system under the expression of eye and brain specific driver. Over expression of Ago-1 resulted in reduced number of ommatidia in the eye and produced smaller size brain in adult and larval Drosophila. A drastic reversal of the phenotype towards normal was observed upon introduction of a single copy of the dominant negative mutation of basket (bsk, Drosophila homolog of JNK) indicating an active and physical involvement of the bsk with Ago-1 in inducing developmental apoptotic process. Further study showed that Ago-1 stimulates phosphorylation of JNK through transforming growth factor-? activated kinase 1- hemipterous (Tak1-hep) axis of JNK pathway. JNK phosphorylation results in up regulation of pro-apoptotic genes head involution defective (hid), grim & reaper (rpr) and induces activation of Drosophila caspases (cysteinyl aspartate proteinases);DRONC (Death regulator Nedd2-like caspase), ICE (alternatively Drice, Death related ICE-like caspase) and DCP1 (Death caspase-1) by inhibiting apoptotic inhibitor protein DIAP1 (Death-associated inhibitor of apoptosis 1). Further, Ago-1 also inhibits miR-14 expression to trigger apoptosis. Our findings propose that Ago-1 acts as a key regulator in controlling cell death, tumor regression and stress response in metazoan providing a constructive bridge between RNAi machinery and cell death.